PERILAKU MENGGARAM GAJAH SUMATERA (Elephas maximus sumatranus) DI PUSAT KONSERVASI GAJAH TAMAN NASIONAL WAY KAMBAS - Riba 'i; Agus Setiawan; Arief Darmawan (Tengkawang : Jurnal Ilmu Kehutanan, 2012)
This research is purposed to find out the sumateranus elephants natural salting behavior and to find out the salt content in the soli in sumateranus elephants salt licks by used exploration method. The result of the research shows that adult male and female of sumateranus elephant have the same natural salting behaviour. The natural salting bahaviour is divided into 4 division based on the shepherding place, the are swamp, savannah, edge, and mudhole. Salting frequency is influenced by 3 factors they are the availability of woof, condition of health, and weather. The longest salting duration in mudhole. The way of salting is utilizing organs among others: trunk, tusks, ang feet. The average of salt inside the soil in salting place is 0,0133%. Key words: salting behavior, sumateranus elephant, Elephant Conservation Center